PERLINDUNGAN HUKUM ATAS HAK MASYARAKAT HUKUM ADAT TERHADAP PENGELOLAAN LINGKUNGAN HIDUP DI DESA SIKALANG KECAMATAN TALAWI KOTA SAWAHLUNTO PROVINSI SUMATERA BARAT - Muhammad Ikhsan Mukhlis; Maryati Bachtiar; Rahmad Hendra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
This research relates to legal protection of the rights of indigenouspeoples to environmental management in Sikalang Village, Talawi District,Sawahlunto City. Coal mining activities have an impact on environmental damageto customary law communities. Therefore it is necessary to examine first, legalprotection of the rights of the legal community to environmental management inSikalang Village, secondly the constraints on legal protection of the rights ofindigenous peoples to environmental management in Sikalang Village, thirdlyefforts in legal protection of the rights of indigenous peoples to managementenvironment in Sikalang Village.This research is a sociological legal research, because it is based on fieldresearch, namely by collecting data from observations, interviews, questionnaires,and literature studies that have to do with problems using qualitative dataanalysis, producing descriptive data, and concluded with a deductive thinkingmethod.From the results of the study, it was concluded that, first, the legalprotection of the rights of indigenous peoples to environmental management inSikalang Village, Talawi District, Sawahlunto City has not been maximized asexpected by Law Number 32 of 2009 concerning Environmental Protection andManagement. Second, the obstacle in legal protection of the legal community'srights to environmental management in Sikalang Village, Talawi District,Sawahlunto City is the position of indigenous peoples who are considered to bestill low in obtaining justice. The three efforts to obtain legal protection for thelegal community's rights to environmental management in Sikalang Village,Talawi District, Sawahlunto City continue to be pursued by both theenvironmental service and the local customary law community, especially inpreserving local wisdom.Keywords: Legal Protection – Indigenous Peoples - Environment